The relationship between the level of knowledge, documentation, and communication of nurses with the intra-hospital transfer process: A literature review - Masniari Juliana Siregar; Yufitriana Amir; Bayhakki Bayhakki (Malahayati International Journal of Nursing and Health Science, 2024)
Background: The intra-hospital transfer process is the transfer of patients while being treated in hospital from one service or from one inpatient unit to various other service units.Transfer is the transfer of a patient within the same facility for diagnostic procedures or transfer to another room to receive additional treatment. Purpose: This literature review aims to review previous research regarding the relationship between the level of knowledge, documentation and communication of nurses with the intra-hospital transfer process. Method: This literature review uses electronic databases such as PubMed, Google Scholar, Wiley Online Library, and Springer Link, which are journals published for the period 2016 to 2023. Articles were filtered using prism diagram rules, the keywords used in the literature search were "patient transfer" AND “intra-hospital” OR “intra-hospital patient transfer”. Results: There were 9 pieces of appropriate literature, which were then analyzed and the results showed that the importance of the role of nurses in patient safety during the transfer phase of patient care includes policies, clinical processes, quality of information, accuracy and coordination of nurses, doctors and other staff in filling out transfer forms and communication in internal so that it can affect quality in terms of accuracy. Conclusion: Implementation of a good transfer process is influenced by several factors, including pre-transfer preparation and stabilization, knowledge and skills of transfer accompanying nurses, necessary equipment and monitoring, patient documentation and handover, effective communication and having transfer guidelines. The patient transfer process can run smoothly, but poor implementation of nurses' knowledge, documentation and communication regarding patient transfers can hamper the transfer process which can result in morbidity, mortality and patient safety incidents. Suggestion: The transfer process can threaten patient safety, this is because the transfer situation is prone to incidents due to the duration of the transfer, severity of illness, lack of experience of accompanying health workers, and communication gaps. So effective communication, collaboration, standardization and implementing appropriate care are needed. This emphasizes the important role of nurses in patient safety during the transfer phase of patient care.